Estrategias lúdicas para la enseñanza-aprendizaje de la lectoescritura en los niños del tercer año de Educación General Básica de la Unidad Educativa “Jorge Washington”. - Oña Cayo, Mayra Angélica (2021)
The present investigation was framed in Playful Strategies for the teaching-learning of the literacy of the children of the Third year of Basic General Education of the Jorge Washington Educational Unit, the methodology that was used was with a mixed approach since its objective was to verify the theories found in the place where the investigation was applied as well as the prosecution. The execution of the project was feasible because bibliographic information taken from several previous works was used, the diagnosis was made and its application in the place under investigation because the problem statement describes the need that children have to improve development of the literacy process through playful strategies through a proposal focused on a specific objective. This led to the design of playful strategies and practical activities with games for the teaching-learning of literacy in children in the third year, which was socialized with the teachers who work in the elementary sublevel and applied with the students of the third year of Education. Basic General. It was validated by criteria of experts with high experience in the educational field and in the area of Language and Literature, finally it was applied as an alternative solution to the teaching-learning process of literacy and with its application an improvement and strength in the children and expanding attention and concentration in literacy development.